2021
DOI: 10.3390/cancers13051121
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Next-Generation Sequencing-Based Panel Testing under the Universal Health-Care System in Japan: A Retrospective Analysis at a Single University Hospital

Abstract: Next-generation sequencing (NGS) assay is part of routine care in Japan owing to its reimbursement by Japan’s universal health-care system; however, reimbursement is limited to patients who finished standard treatment. We retrospectively investigated 221 patients who underwent Foundation One CDX (F1CDx) at our hospital. Every F1CDx result was assessed at the molecular tumor board (MTB) for treatment recommendation. Based on patients’ preferences, presumed germline findings were also assessed at the MTB and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 36 publications
1
13
3
Order By: Relevance
“…The other patient characteristics (age, gender, ECOG-PS, number of prior systemic therapies, and distance from patient's homes to the NCCH) were not associated with receiving genomically matched therapy. 10,11 Our rate of 12.2% seems to be higher than those previously reported at the other sites in Japan. A major reason for this is that the largest number of IND trials (mainly industry sponsored trials) are conducted at our site in Japan.…”
Section: Common and Non-common Cancerscontrasting
confidence: 74%
See 1 more Smart Citation
“…The other patient characteristics (age, gender, ECOG-PS, number of prior systemic therapies, and distance from patient's homes to the NCCH) were not associated with receiving genomically matched therapy. 10,11 Our rate of 12.2% seems to be higher than those previously reported at the other sites in Japan. A major reason for this is that the largest number of IND trials (mainly industry sponsored trials) are conducted at our site in Japan.…”
Section: Common and Non-common Cancerscontrasting
confidence: 74%
“…NRG1 fusion found in 1 patient was only detected by the OncoGuide™ NCC Oncopanel System, and RAF1 rearrangement found in 1 patient was only detected by the FoundationOne® CDx Cancer Genomic Profile. Kikuchi et al (2021) and Inagaki et al (2021) reported that 11.1% (21 of 189 patients) and 3.6% (6 of 221 patients) of patients received genomically matched therapy after CGP tests, respectively 10,11 . Our rate of 12.2% seems to be higher than those previously reported at the other sites in Japan.…”
Section: Discussioncontrasting
confidence: 45%
“…Additionally, in some cases, insurance companies agreed to cover expenses for off-label treatment only conditionally after failure of several lines of therapy, a situation in which patients are often unlikely to draw clinical benefit. Our preliminary data therefore support the notion that NGS testing should be taken into consideration rather early in the course of a disease in order to avoid the waiving of possible matched therapies due to compromised patient performance status after several lines of therapy [ 61 ].…”
Section: Discussionsupporting
confidence: 71%
“…These studies prompted FoundationOne CDx to become a companion diagnostic for capmatinib for MET-dysregulated NSCLC. [34][35][36] Utilization of FoundationOne CDx as a companion diagnostic for other driver mutations in other solid tumors is currently being investigated, with mixed results suggesting potential applications in glioma and breast but limited utility in pancreatic ductal adenocarcinoma. [37][38][39]…”
Section: Foundationone ® CDX As the Companion Diagnostic For Capmatinib In Metex14 Nsclcmentioning
confidence: 99%